Musical perception and cognitive functions. Is there such a thing as the Mozart effect? (2004)
Introduction. Throughout the second half of the 20th century important advances were made in the study of neurobiology related to the processing of music, the differences and similarities between the neural pathways involved in language and in music, the role played by each hemisphere in recognising these stimuli, and the effects that exposure to certain specific pieces of music could have on the cognitive functions. Development. The objective of this study is to review the literature concerning music and the central nervous system, bearing in mind the above-mentioned aspects. Likewise, we also wanted to analyse the reports referring to the Mozart effect and Tomatis, in addition to those dealing with formal musical education and its effects. The increased capacity to respond in visuospatial-type tasks after exposure to music by Mozart has triggered a commercial boom which makes use of isolated data, while the real extent of the effect remains unknown. Conclusions. After reviewing the scientific literature on this subject, it was found that the effects of exposure to music by Mozart (the 'Mozart effect') when they actually occurred, were limited to a specific skill that did not last for more than a few minutes. Formal musical education, on the other hand, shows more permanent positive effects but which can be attributed to the individual attention the pupil receives and to the stimulation in basic skills for general learning. © 2004, Revista De Neurología.